The Mechanisms of Formation of Demand in the High-Tech Products Market - Derunova, Elena; Semenov, Alexandr; Balash, Olga; Firsova, Anna (International Journal of Economics and Financial Issues, 2016)
Currently, high technologies are a key factor and catalyst for technological modernization of the Russian economy. Effective management and development of high technologies market is the key to the transition from commodity to high-tech development. The article considers the factors influencing the dynamics of the demand for high technologies in the light of scientific and technical progress. The indicators of competitiveness of high technologies on Russian and foreign markets is studied, developed approaches to generate demand for high technologies and conceptual model of sales management of innovation technology products. Scorecard to build a matrix of decision making in marketing is justified and generated sales management mechanisms of high technologies on the market high-tech products and presents practical advice on creating demand for high technologies in the B2B market. Keywords: high technology, high-tech product, marketing of high technologies, innovation, consumer behavior, formation of demand, economic growth JEL Classifications: O; O3; Q55